THE EFFECT OF ENGAGING ISLAMIC EDUCATION AND MUHAMMADIYAHISM IN CHARACTER BUILDING AMONG MUHAMMADIYAH’S SENIOR HIGH SCHOOL STUDENTS IN BOGOR - Madropi, Madropi; Saefuddin, Didin; Bahruddin, E (Tawazun: Jurnal Pendidikan Islam, 2018)
Islamic education and Muhammadiyahism is one of the integrated education processes in the form of building human’s characters well. This effort is unreachable when those people are not aware the importance of both educational systems. The aim of the research is to recognize the effectiveness of engaging Islamic education in characters building among Muhammadiyah senior high school students. The research method is a survey using a questionnaire based on the variables: Islamic religion science (X1), Muhammadiyah’s education (X2), and student’s characters building (Y). The respondents are Muhammadiyah Senior High School student.s. The result of the research is only for the internal purpose of Muhammadiyah Senior High School, South Bogor. 56 samples consisting of students of grade X and grade XI followed 2 semesters of religion class. The research was exclusively done among Muhammadiyah Senior High School students, so the result is only for research population to support Islamic education and Muhammadiyahism to become better in the future. Keywords : Character Building, Islamic Education, Muhammadiyahism